A comprehensive framework for multibody system analysis with clustered cables: examples of tensegrity structures. (February 2021) - Kan, Ziyun; Song, Ningning; Peng, Haijun; Chen, Biaosong; Song, Xueguan
Abstract: Structures with clustered cables are widespread in many engineering applications. Most existing works involving clustered cables are based on a finite element formulation and do not address cable friction. This paper presents a novel multibody-based methodology for the mechanical analysis of systems containing clustered cable elements. The generalized coordinates of the system are chosen as configurations of the attached rigid bodies, rather than traditional nodal displacements or positions on the finite element formulation. The clustered cables are considered as internal force elements that act on the bodies. To address the friction induced by cable sliding, a comprehensive complementarity-based framework is developed for different analysis cases. For explicit dynamic analyses, by introducing a limited number of assumptions, a non-smooth LCP-based approach is proposed that enables us to integrate any mature LCP solvers into the time integration. For implicit static and dynamic analyses, a nonlinear complementarity function-based approach is proposed, which allows us to solve the problem in a unified, continuous and smooth manner. As a representative engineering application, the developed framework is employed in the mechanical analyses of active tensegrity structures. The numerical results show that the friction between the clustered cable and the struts fundamentally alters the system mechanical behavior. For static analyses, it is emphasized that friction leads to a significant difference in tension magnitudes in different segments of a clustered cable. For dynamic analyses, the results reveal that novel behavior, such as the stick–slip phenomenon of the connection points can occur frequently. The outcomes demonstrate the ability of the proposed methodology to capture the complex and diverse motion states.